Porous evaporators with special wettability for low-grade heat-driven water desalination - Zhu, Zhigao (2021)
Against the backdrop of global water scarcity, porous interface distillation (PID) working on macroporous evaporation materials attracts ever-growing attention in sustainable desalination. It excels itself in the ability to treat high-salinity brines and employ low-grade heat energy from industrial sources or solar energy, as well as low installation complexity and cost. In recent years, PID evaporators with special wettability, such as omniphobicity, asymmetric superwettability, superhydrophobicity and superhydrophilicity, are especially effective in improving distillation efficiency and operation lifetime, and much progress is made in this aspect. To provide a comprehensive overview, this review puts forward a panoramic discussion on the recent progress of hydrophobic and hydrophilic porous evaporators with special wettability for low-grade heat-driven water desalination, with focuses on material and structural designs to improve distillation efficiency and long-term durability. Current challenges and future perspectives are also provided as a guide for future research towards the practical application of PID for sustainable water desalination.